Phenotype of subsyndromal delirium using pooled multicultural Delirium Rating Scale—Revised-98 data - Trzepacz, Paula T.; Franco, Jose G.; Meagher, David J.; Lee, Yanghyun; Kim, Jeong-Lan; Kishi, Yasuhiro; Furlanetto, Leticia M.; Negreiros, Daniel; Huang, Ming-Chyi; Chen, Chun-Hsin; Kean, Jacob; Leonard, Maeve (Journal of psychosomatic research, 2012)
There is no consensus definition for the phenotype of subsyndromal delirium (SSD), a subthreshold state to full delirium. Without an a priori definition we applied advanced analytic techniques to discern SSD. We pooled Delirium Rating Scale—Revised-98 (DRS-R98) data from 859 DSM-IV diagnosed nondemented delirious adults and nondelirious controls collected by investigators in 7 countries. Discriminant analyses defined an SSD group that was then compared to Nondelirium and Delirium groups. SSD (n=138) had intermediate DRS-R98 item severities between Delirium (n=497) and Nondelirium (n=224) groups, where groups significantly differed on all DRS-R98 items (ANOVA p<.001) except delusions. Discriminant analysis found SSD phenomenologically closer to Delirium than Nondelirium. Using full multinomial logistical regression, SSD was distinguished from Nondelirium by temporal onset, sleep–wake cycle, perceptual disturbances, motor retardation, delusion, affective lability, and all cognitive items; SSD was similar to Delirium in thought process, language, motor agitation or retardation, sleep–wake cycle, all cognitive items, fluctuation and physical disorder. The multivariate model correctly classified 94.2% of Nondelirium, 75.4% of SSD and 97.2% of Delirium subjects. Binary logistic regression of six core domain symptoms (sleep–wake cycle, thought process, language, attention, orientation, and visuospatial ability) together were found as highly differentiating of SSD from Nondelirium, which correctly classified almost 80% of SDD. SSD is intermediate in severity between nondelirious controls and full syndromal delirium, but its phenotype is more like delirium. Core domain delirium symptoms present at milder severity in SSD should be evaluated further for utility in detecting and managing SSD, preventing delirium, and possible inclusion in DSM-V.